2021
DOI: 10.3389/fnins.2021.648814
|View full text |Cite
|
Sign up to set email alerts
|

Time Distortion in Parkinsonism

Abstract: Although animal studies and studies on Parkinson’s disease (PD) suggest that dopamine deficiency slows the pace of the internal clock, which is corrected by dopaminergic medication, timing deficits in parkinsonism remain to be characterized with diverse findings. Here we studied patients with PD and progressive supranuclear palsy (PSP), 3–4 h after drug intake, and normal age-matched subjects. We contrasted perceptual (temporal bisection, duration comparison) and motor timing tasks (time production/reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 103 publications
3
20
1
Order By: Relevance
“…The current results potentially contribute to the understanding of arithmetic, language processing, and temporal processing. Clinically, the deficiencies of these functions were frequently observed in patients with various psychiatric conditions such as dementia, depression, Parkinson’s disease, and autism ( Folstein, Folstein & McHugh, 1975 ; Kjelgaard & Tager-Flusberg, 2001 ; Casassus et al, 2019 ; Buciuc et al, 2021 ; Terao et al, 2021 ; Yeung et al, 2021 ). Furthermore, the cognitive impairments in these disorders are known to appear in complex combinations rather than in a fixed pattern ( American Psychiatric Association, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results potentially contribute to the understanding of arithmetic, language processing, and temporal processing. Clinically, the deficiencies of these functions were frequently observed in patients with various psychiatric conditions such as dementia, depression, Parkinson’s disease, and autism ( Folstein, Folstein & McHugh, 1975 ; Kjelgaard & Tager-Flusberg, 2001 ; Casassus et al, 2019 ; Buciuc et al, 2021 ; Terao et al, 2021 ; Yeung et al, 2021 ). Furthermore, the cognitive impairments in these disorders are known to appear in complex combinations rather than in a fixed pattern ( American Psychiatric Association, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temporal processing is one of the cognitive domains related to temporal dimensions. It is often impaired by several psychiatric diseases, such as a bipolar disorder, Parkinson’s disease, dementia, and autism ( Folstein, Folstein & McHugh, 1975 ; Kuhs et al, 1991 ; Kjelgaard & Tager-Flusberg, 2001 ; Mahlberg et al, 2008 ; Casassus et al, 2019 ; Buciuc et al, 2021 ; Terao et al, 2021 ; Yeung et al, 2021 ). Temporal processing is sometimes divided into two sub-categories: sub-second intervals and supra-second intervals (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…A so-called Weber ratio (WR) quantified variability in responses, PD subjects tended to underestimate time and to exhibit widely distributed individual WR's, the latter suggesting lower sensitivity to time estimation generally. Reminiscent of Malapani et al ( 17 ), Terao et al ( 72 ) found that time reproduction of very short time durations was longer in PD subjects [and even longer in Progressive Supranuclear Palsy (PSP) subjects] and shorter for long-time durations (even shorter in PSP). Terao et al's methodology included various tests in concert with time reproduction tasks.…”
Section: Clinical Literature Reviewmentioning
confidence: 95%
“…Aberrant time perception in PD could provide some insight into disease progression and severity. Perceptual error in auditory duration comparison correlated with mini-mental state examination (MMSE) score in a recent study (Terao et al, 2021), and should be studied longitudinally in a prospective cohort study. Additionally, these deficits may exhibit consistent treatment effects: two studies have shown improvements of deep brain stimulation of the subthalamic nucleus (STN DBS) on time perception in auditory interval discrimination at subsecond time scales, and motor time production at suprasecond timescales (Koch et al, 2004;Guehl et al, 2008).…”
Section: Developing Cognitive Biomarkers For Parkinson's Diseasementioning
confidence: 99%